Variations of peroneus tertius muscle in five Arab populations: A clinical study - Abdel Halim Salem; Ghada Abdel Kader; Amani A. Almallah; Hoda H. Hussein; Ahmed Abdel Badie; Nadiah Behbehani; Fatema N. Nedham; Ayesha N. Nedham; Reem Almarshad; Munirah Alshammari; Hanine Amer; Wafa A. Hasan; et al. (Elsevier, 2018)
Introduction: Peroneus tertius (PT) is greatly variable muscle and may be absent. PT muscle marks the anterolateral entry during using the ankle arthroscopy, used as a flap to cover defects in the foot soft tissue, tendon transfer and resection surgeries. PT may have a role in ankle joint injuries. The present study was conducted to evaluate the prevalence of PT muscle in five Arab populations and its relation to ankle joint injury. Materials and methods: The presence of PT was clinically determined in five Arab countries (439 Bahraini, 208 Saudi, 153 Kuwaiti, 198 Tunisians and 250 Egyptians) using standard technique. Results: The prevalence of PT was observed in 42%, 38.5% and 41.2% in Asian populations (Bahraini, Saudi and Kuwaiti population, respectively) whereas, the African populations (Tunis and Egypt) revealed higher frequency (67.7% and 52.8%, respectively). The highest prevalence of PT occurred in males in Saudi Arabia and Egypt and females in Bahrain, Kuwait and Tunisia. Right limbs showed the most prevalent side in all populations except Bahrainis with increased prevalence of bilateral presence in all populations. PT was easily detected in Saudi and Tunisians followed by Bahrainis and Kuwaitis whereas, Egyptians revealed difficulty in PT detection. A significant correlation between the PT muscle and the occurrence of ankle injury was observed in all studied populations. Conclusion: PT showed variable prevalence in different populations in the world. There is a positive correlation between ankle injuries and PT presence. Further cadaveric and imaging studies are needed to study the PT variations. Keywords: Peroneus tertius muscle, Variation, Arab populations